The Impact Of Profitability Ratios On The Timeliness Of Financial Reporting - Guna Ismawan; Wiwit Pawitri; Muhammad Syahrudin (Journal of Accounting Inaba, 2024)
Information delays will have a negative impact on the company, because the information in the financial statements contains good news and bad news that can influence investment decisions. The purpose of this study was to determine how the influence of the Profitability Ratio on the Timeliness of Financial Reporting in Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period. The method used in this research is quantitative using associative descriptive research. The sampling technique used in this study used purposive sampling technique. Samples in the study obtained through sample selection criteria obtained 9 manufacturing companies with a total of 45 samples. The data source obtained from this research is secondary using financial reports from 9 companies according to the sampling criteria from 2018 to 2022. Logistic Regression Analysis was used in this study. The results showed that ROA, ROE had no partial or simultaneous effect on the timeliness of reporting financial statements in manufacturing companies listed on the IDX for the period 2018 to 2022.